Efficacy of mHealth aided 12-week meditation and breath intervention on change in burnout and professional quality of life among health care providers of a tertiary care hospital in north India: a randomized waitlist-controlled trial - Bhardwaj, Praag; Pathania, Monika; Bahurupi, Yogesh; Kanchibhotla, Divya; Harsora, Prateek; Rathaur, Vyas Kumar (Frontiers in Public Health, 2023)
Introduction: Burnout is "Chronic workplace stress that has not been successfully managed". Professional quality of life (PQL) includes work related experiences of compassion satisfaction and compassion fatigue. Healthcare providers (HCPs) are highly susceptible to burnout and compassion fatigue due to their demanding work, which lowers PQL. Burnout leads to poor care, medical errors, and patient safety across healthcare disciplines. Yoga has been shown to improve resilience, reduce stress, and increase self-compassion and psycho-physiological coherence. This study compared HCPs in a mHealth-aided 12-week yoga-based meditation and breath intervention to waitlist controls for HCP burnout and PQL at a north Indian tertiary care hospital. Methods: This was randomized waitlist-controlled trial. Total 98 HCPs (62 males and 36 females) with an average age of 28.26±3.547 years were enrolled consecutively from March 2021 to November 2022. Randomization was done with opaque sealed envelopes numbered in a computer-generated sequence. The experimental group (n=49) received 12 online weekly yoga sessions and performed daily home practice (6 days a week). The waitlisted control group (n=49) continued their daily routine. Maslach’s burnout inventory (MBI), professional quality of life (PQL) and anthropometric measurements were assessed at baseline and after 12 weeks. Results: After 12 weeks, the MBI outcomes of emotional exhaustion, depersonalization, and personal accomplishment showed a highly significant difference between the two groups (p<0.001). PQL outcomes of compassion satisfaction, burnout, and secondary trauma also differed significantly (p<0.001). Within group analysis showed that MBI and PQL outcomes improved significantly (p<0.001) for the experimental group after 12 weeks. Conclusion: The current study contributes to the existing evidence on the effectiveness of Yoga in managing stress and developing resilience among doctors, nurses, and other medical professionals. Integrating yoga into healthcare settings is crucial for addressing the detrimental impact of burnout on decision-making and promoting positive patient outcomes. mHealth technologies have the potential to enhance the user-friendliness of yoga-based interventions by personalizing the practice space and time. Yoga-based interventions and mHealth technologies can effectively address physician burnout, in a simple and implementable manner.